Diversity of Merozoite Surface Protein-3β Gene of Plasmodium vivax Isolates from Iran - A Shahbazi; A Raeisi; M Nateghpour; H Mirhendi; M Mohebali; M Asmar (Tehran University of Medical Sciences, 2007)
Background: Plasmodium vivax malaria accounts for approximately 88% of malaria cases in Iran. There is limited information on genetic diversity of P. vivax in the country and a need to develop and apply an effective vaccine against the disease is necessary. Among many potential candidates, MSP -3β gene is promising target. This study was designed and carried out to determine the variation of this gene as genetic marker in population of malarious areas of Iran.Methods: Blood sample of 85 P. vivax isolates from four southern and east-southern provinces of the country assessed for polymorphism of PvMSP-3β gene by PCR/RFLP method. Results:  Based on the size of PCR product of the gene, 7 genetically different types of parasite has been distinguished. Two alleles were simultaneously visible in 19 % of the cases. Results from PCR/RFLP analysis of PvMSP-3β gene showed at least 15 allelic groups. Multiple infections have been found in 2.4 % of the cases. Conclusion: PvMSP-3β gene was highly diverse in P. vivax isolates of malarious areas of Iran, and can be a suitable marker for population genetic studies of P. vivax. More investigations on PvMSP-3β genes are needed to reveal genetic structure of P. vivax in Iran.